The Impact of Quran Memorization Habit on Students' Desire to Learn The Arabic Language at The Secondary School Level in The "Al-Quran Harsallakum" Islamic Boarding School Bengkulu - Akhirudin, Akhirudin; Meldania, Meldania; Ni’am, Falahun (Borneo Journal of Language and Education, 2023)
The objectives of this research are to determine the impact of Quran memorization habit on the interest in learning the Arabic language at the secondary school level in the "Al-Quran Harsallakum" Islamic boarding school, Bengkulu. This research adopts a quantitative descriptive research design. The research was conducted at the secondary school level in the "Al-Quran Harsallakum" Islamic boarding school, Bengkulu in June 2021. Data was collected through observation, documentation, and questionnaires. The research findings, titled "The Impact of Quran Memorization Habit on Students' Interest in Learning the Arabic Language," revealed a strong relationship between Quran memorization habit and the desire to learn the Arabic language at the secondary school level in the "Al-Quran Harsallakum" Islamic boarding school, Bengkulu.